The Effects of Age and Season on Semen Characteristics of White Leghorn Cocks under Sudan Conditions - Elagib, H.A.A.; Musharaf, N.A.; Makawi, S.A.; Mohamed , H.E. (International Journal of Poultry Science, 2011)
White Leghorn cocks (Bovans) of 2 different ages (1-2 years) were used to study the effect of age and season on semen characteristics. An average of 8 males from each age were used and kept in individual cages in an open sided poultry house for 6 months. Average maximum and minimum daily temperature during summer and autumn seasons were 40.3, 24.4 and 39.3, 26.1, respectively. Semen was collected weekly by abdominal massage and evaluated for semen volume, motility, concentration and percentage of dead and abnormal spermatozoa. There was a significant difference (p<0.05) between the two age groups in semen volume 0.22±0.02 and 0.29±0.25 mL; mass motility scores were 3.56±0.06 and 3.17±0.08 and the percentage of abnormal sperm 4.67±0.14 and 5.62±0.16% for one and 2 years, respectively. No significant difference was found in sperm concentration or percentage of dead sperms. Summer season caused a significant drop in semen volume by 8.7% in one year old and sperm concentration in two years old by 19.7%. It is also, caused an increase in percent dead sperm by 40.86 and 41.89% in 1 and 2 years, respectively.